An Empirical Analysis of the Relationship between Economic Growth and Credit Volumes in Hungary - Varga, József; Temuulen, Elbegdorj; Bareith, Tibor (Public Finance Quarterly, 2019)
Our research focuses on the impact of the private sector’s credit volume on economic growth. The main purpose of our study is to present the theoretical background between lending activity and economic growth, which is empirically tested for Hungary in 2000-2017. We have used the Vector Autoregression model, where the dependent variable is a linear function of past lags of itself and past lags of the other involved variables. We have identified a significant relationship between private sector credit and general government debt and the pace of economic growth. Based on our empirical research, the base effect, Germany’s economic growth and recession were significant variables.